Strategi Pemasaran Produk Pembiayaan Mitra Usaha Ib melalui Pendekatan Personal Selling di BPRS Mitra Mentari Sejahtera Ponorogo - Aditya, Rian; Said Abadi (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: BPRS Mitra Mentari Sejahtera has implemented personal selling as a marketing method, but according to data obtained by researchers, iB business partner financing products have not experienced an increase in the number of customers. So this research shows that personal selling marketing has a less than optimal role in influencing customer interest in using iB Business Partner Financing. Research Methods: This research uses a qualitative approach using field research methods and this type of research is field research and the techniques used are interviews, documentation and observation. Results: The results of this research are BPRS Mitra Mentari Sejahtera in its implementation only applies 5 of the 7 strategies from Kotler and Keller's theory, including prospecting, approach, presentation, handling objections, closing, while the strategies that are not used are preapproach and follow up. The obstacle to the implementation of BPRS Mitra Mentari Sejahtera is the lack of extensive marketing carried out by the bank. Conclusion: this research shows that personal selling marketing has a less than optimal role in influencing customer interest in using iB Business Partner Financing.